Cm-scale marine habitat mapping of entire Tumon Bay, Guam Coral Reef using NASA airborne fluid lensing and NeMO-Net pre (2022) and post (2024) Typhoon Mawar - Soufyane Bouchelaghem; Ved Chirayath; Imad Eddine Tibermacine; Alexandra C. Dempsey; Sam J. Purkis (Frontiers in Marine Science, 2026)
Introduction High-resolution imaging of coral reefs is critical for understanding ecosystem dynamics and guiding conservation efforts yet monitoring these changes at ecologically relevant spatial and temporal scales remains challenging. Methods We present cm-scale benthic habitat maps for over 5 km 2 of coral reefs in Tumon Bay, Guam, for 2022 and 2024, before and after Category 4 Typhoon Mawar (May 2023). NASA Airborne Fluid Lensing data were combined with in-situ ground-truthing and citizen-science annotations from the NeMO-Net platform. NeMO-Net’s original CNN was modified to an Attentive Residual U-Net (ARU-Net) with an EfficientNet-B3 encoder, class-weighted loss, and attention gating to classify seven habitat classes at pixel (cm) scale, using only ~1% of the 2022 dataset for training. Results Our model achieved 88% overall pixel-scale accuracy across seven ecologically relevant benthic classes. Full-coverage habitat maps for 2022 and 2024 reveal a 59% decline in massive coral, a 35% decline in coral fore-reef, and a 105% increase in algal cover, providing spatially explicit evidence of Typhoon Mawar’s reef impact. Discussion Coupling Fluid Lensing imagery with the NeMO-Net citizen-science platform and a modified ARU-Net yields accurate cm-resolved habitat assessments from sparse labels, supporting timely evaluation of disturbance and restoration outcomes in complex shallow-water reef environments.

Using Tourist Diver Images to Estimate Coral Cover and Bleaching Prevalence in a Remote Indian Ocean Coral Reef System - Anderson B. Mayfield; Alexandra C. Dempsey (Oceans, 2025)
Citizen science approaches for monitoring, and even restoring, coral reefs have grown in popularity though tend to be restricted to those who have taken courses that expose them to the relevant methodologies. Now that cheap (~10 USD), waterproof pouches for smart phones are widely available, there is the potential for mass acquisition of coral reef images by non-scientists. Furthermore, with the emergence of better machine-learning-based image classification approaches, high-quality data can be extracted from low-resolution images (provided that key benthic organisms, namely corals, other invertebrates, & algae, can be distinguished). To determine whether informally captured images could yield comparable ecological data to point-intercept + photo-quadrat surveys conducted by highly proficient research divers, we trained an artificial intelligence (AI), CoralNet, with images taken before and during a bleaching event in 2015 in Chagos (Indian Ocean). The overall percent coral covers of the formal, “gold standard” method and the informal, “tourist diver” approach of 38.7 and 35.1%, respectively, were within ~10% of one another; coral bleaching percentages of 30.5 and 31.8%, respectively, were statistically comparable. Although the AI was prone to classifying bleached corals as healthy in ~one-third of cases, the fact that these data could be collected by someone with no knowledge of coral reef ecology might justify this approach in areas where divers or snorkelers have access to waterproof cameras and are keen to document coral reef condition.

Atypical disseminated herpes zoster infections in patients with demyelinating disease treated with dimethyl fumarate - Alexandra Balshi; John Dempsey; Jacob A. Sloane (Journal of NeuroVirology, 2024)

Remotely sensed habitat diversity predicts species diversity on coral reefs - Anna C. Bakker; Arthur C.R. Gleason; Alexandra C. Dempsey; Helen E. Fox; Rebecca H. Green; Sam J. Purkis (Remote Sensing of Environment, 2024)

Environmentally-Driven Variation in the Physiology of a New Caledonian Reef Coral - Anderson B. Mayfield; Alexandra C. Dempsey (Oceans, 2022)
Given the widespread threats to coral reefs, scientists have lost the opportunity to understand the basic biology of “pristine” corals whose physiologies have not been markedly perturbed by human activity. For instance, high temperature-induced bleaching has been occurring annually since 2014 in New Caledonia. Because most corals cannot withstand repeated years when bleaching occurs, an analysis was undertaken to showcase coral behavior in a period just before the onset of “annual severe bleaching” (ASB; November 2013) such that future generations might know how these corals functioned in their last bleaching-free year. Pocillopora damicornis colonies were sampled across a variety of environmental gradients, and a subset was sampled during both day and night to understand how their molecular biology changes upon cessation of dinoflagellate photosynthesis. Of the 13 environmental parameters tested, sampling time (i.e., light) most significantly affected coral molecular physiology, and expression levels of a number of both host and Symbiodiniaceae genes demonstrated significant diel variation; endosymbiont mRNA expression was more temporally variable than that of their anthozoan hosts. Furthermore, expression of all stress-targeted genes in both eukaryotic compartments of the holobiont was high, even in isolated, uninhabited, federally protected atolls of the country’s far northwest. Whether this degree of sub-cellular stress reflects cumulative climate change impacts or, instead, a stress-hardened phenotype, will be unveiled through assessing the fates of these corals in the wake of increasingly frequent marine heatwaves.

The Prospect of Global Coral Reef Bathymetry by Combining Ice, Cloud, and Land Elevation Satellite-2 Altimetry With Multispectral Satellite Imagery - Arthur C. R. Gleason; Ross Smith; Sam J. Purkis; Kyle Goodrich; Alexandra Dempsey; Alejandro Mantero (Frontiers in Marine Science, 2021)
Empirical methods for estimating shallow-water bathymetry using passive multispectral satellite imagery are robust and globally applicable, in theory, but they require copious local measurements of water depth for algorithm calibration. Such calibration data have historically been unavailable for most locations, but NASA’s Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2), a satellite-based LiDAR, might hold unique promise to fill this critical data gap. Although ICESat-2 was not designed as a marine altimeter, its ATLAS sensor consists of six green (532 nm) lasers that can penetrate a water surface and return photons reflected by the seabed, thereby generating bathymetric profiles. Utilizing TCarta’s NSF SBIR-funded Space-Based Laser Bathymetry Extraction Tool and ICESat-2’s ATL03 geolocated photon data product, we have compared ICESat-2 bathymetric retrievals with a portfolio of soundings acquired in situ using a vessel-mounted single-beam echosounder. This analysis demonstrated very high correlation ( R 2 = 0.96) between the field and space-based bathymetry data. The comparisons were made at multiple Caribbean and Pacific coral reef sites over water depths ranging from 1 to 20 m. Results suggest that ICESat-2 could be an effective approach for calibrating and validating empirical and radiative transfer methods, alike, for estimating shallow-water bathymetry from remote sensing imagery, thereby enabling the immediate potential for shallow-water bathymetric mapping of Earth’s reefs.

Revisiting the paradigm of shark‐driven trophic cascades in coral reef ecosystems - Amelia A. Desbiens; George Roff; William D. Robbins; Brett M. Taylor; Carolina Castro‐Sanguino; Alexandra Dempsey; Peter J. Mumby (Ecology, 2021)
Global overfishing of higher‐level predators has caused cascading effects to lower trophic levels in many marine ecosystems. On coral reefs, which support highly diverse food webs, the degree to which top‐down trophic cascades can occur remains equivocal. Using extensive survey data from coral reefs across the relatively unfished northern Great Barrier Reef (nGBR), we quantified the role of reef sharks in structuring coral reef fish assemblages. Using a structural equation modeling (SEM) approach, we explored the interactions between shark abundance and teleost mesopredator and prey functional group density and biomass, while explicitly accounting for the potentially confounding influence of environmental variation across sites. Although a fourfold difference in reef shark density was observed across our survey sites, this had no impact on either the density or biomass of teleost mesopredators or prey, providing evidence for a lack of trophic cascading across nGBR systems. Instead, many functional groups, including sharks, responded positively to environmental drivers. We found reef sharks to be positively associated with habitat complexity. In turn, physical processes such as wave exposure and current velocity were both correlated well with multiple functional groups, reflecting how changes to energetic conditions and food availability, or modification of habitat affect fish distribution. The diversity of species within coral reef food webs and their associations with bottom‐up drivers likely buffers against trophic cascading across GBR functional guilds when reef shark assemblages are depleted, as has been demonstrated in other complex ecosystems.

High-resolution habitat and bathymetry maps for 65,000 sq. km of Earth’s remotest coral reefs - Sam J. Purkis; Arthur C. R. Gleason; Charlotte R. Purkis; Alexandra C. Dempsey; Philip G. Renaud; Mohamed Faisal; Steven Saul; Jeremy M. Kerr (Coral Reefs, 2019)